Central actions of glucocorticoids in the control of body fluid homeostasis: Review - Ruginsk,S.G. (2009)
The involvement of the hypothalamic-pituitary-adrenal axis in the control of body fluid homeostasis has been extensively investigated in the past few years. In the present study, we reviewed the recent results obtained using different approaches to investigate the effects of glucocorticoids on the mechanisms of oxytocin and vasopressin synthesis and secretion in response to acute and chronic plasma volume and osmolality changes. The data presented here suggest that glucocorticoids are not only involved in the mechanisms underlying the fast release but also in the transcriptional events that lead to decreased synthesis and secretion of these neuropeptides, particularly oxytocin, under diverse experimental conditions of altered fluid volume and tonicity. The endocannabinoid system, through its effects on glutamatergic neurotransmission within the hypothalamus and the nuclear factor κB-mediated transcriptional activity, seems to be also involved in the specific mechanisms by which glucocorticoids exert their central effects on neurohypophyseal hormone synthesis and secretion.